Post-fire phenology in a campo sujo vegetation in the Urucum plateau, Mato Grosso do Sul, Brazil - Neves,DRM. (2011)
Studies on the herbaceous and sub-shrub layer of cerrado showed the occurrence of modifications in its composition between different regions, demonstrating sensibility to changes in climate, soil and intensity of fires, among other factors. The aim of this study was to describe the phenological variation in a campo sujo vegetation in the Urucum plateau. We established eight transects of 250 m each, 50 m apart. We sampled all flowering and fruiting species located at least three meters from each side of the transect. Beginning in October 2007, one month after an accidental fire occurred in the study site, we analysed flowering and fruiting plants in the transects' area. The intensity of the flowering and fruiting phenophases was not uniformly distributed. This study provide us information about the possible fire influence on the reproductive patterns of the community, presenting flowering peaks in October and November, two months after this event. Regression analysis with monthly rainfall also provides us information about the influence of climate data on the flowering and fruiting peaks.